Exploring Sustainable Fuel Production from Waste: A Feasibility Study in Zimbabwe - Clement Shonhiwa Shonhiwa; Simon Chinguwa; Jamerson Kugara (International Journal of Machine Systems and Manufacturing Technology, 2025)
Some organisms are in danger of going extinct, and environmental pollution from waste plastics, tires, and used lubricating oils has significantly contributed to the decline of biodiversity. Tires, plastics, and spent oil all contribute significantly to environmental deterioration, and this issue has been linked to improper treatment and disposal of these materials. Only 15% of the 200 auto technicians surveyed for this study acknowledged that they reuse spent oil, 5% stated they sell it, and 80% acknowledged that they carelessly dump it on the ground. Regarding recycling awareness, 10% said they are aware, 70% said they are ignorant, and 20% said they do not see the need for recycling. When asked how they store used oil, 60% of respondents indicated they do not, 30% said they do so in a metal drum, and 10% said they do it in a plastic drum. About 500 cars are serviced each month, according to the registered motor vehicle mechanics, and 2700 liters of spent oil are produced overall. Due to bad roads, Zimbabwe's transport industry and car owners are changing their tires more regularly. As a result, street merchants burn these worn tires to collect the wires for future sale. The indiscriminate disposal of plastics and used oil tires is therefore a major environmental concern for the Zimbabwean health sector as well as the global community, according to this research. According to this research, Zimbabwe has enough waste plastics, tires, and engine oil that can be converted into 50% cheaper, commercial-grade diesel fuel through pyrolysis and distillation. As a result, less foreign currency that may be utilized for different purposes is required.
Keywords: Waste lubricating oils; distillation; garage; pyrolysis; waste disposal; waste plastics; waste tires